STATE OF THE GUT MICROBIOTA AND THE IMMUNE SYSTEM IN CHILDREN WITH REACTIVE ARTHRITIS IN THE ACUTE PERIOD - Твердохлеб, Т.А. (World of Medicine and Biology, 2016)
The frequency and extent of violations of the intestinal microbiota in children with REA in the acute period was determined. Grade II dysbiosis set to 62,5%, I degree - in 37.5% of children. The peculiarities of immunological homeostasis disorders of patients in acute REA depression of T-Systems and activation of B -system processes of phagocytosis, production of IL-6. Identified reliable direct connections between the content of fungi of the genus Candida, phagocytic links and SD21 and inverse correlation between the number of E. coli and the level of IL-6 content of lactobacilli and spontaneous NBT-test. These results confirm the important role of immune-regulating intestinal microflora in patients with REA were detected.